Glucocorticoid receptor inhibits Th2 immune responses by down-regulating Pparg and Gata3 in schistosomiasis - Sun, Tao; Bi, Xiaojuan; Yang, Ning; Zhang, Xue; Chu, Jin; Li, Liang; Liu, Hui; Tang, Rui; Lin, Renyong (Frontiers in Immunology, 2025)
IntroductionThe Th2 immune response plays a pivotal role in the pathogenesis of schistosomiasis, contributing to the formation of hepatic granulomas and fibrosis. While the glucocorticoid receptor (GR) is a ubiquitously expressed nuclear receptor that mediates anti-inflammatory effects, its impact on Th2 responses in schistosomiasis remains underexplored. Thus, this study aimed to investigate the potential impact of GR activation on the hepatic Th2 immune response in schistosomiasis using the synthetic glucocorticoid dexamethasone.MethodIn vivo, Schistosoma japonicum-infected mice were treated with dexamethasone, while in vitro studies were conducted on Th2 cells. Additionally, RNA sequencing and single-cell sequencing were integrated to identify key transcription factors influenced by GR activation during Th2 cell differentiation, with gene expression levels validated both in vivo and in vitro.ResultsIn vivo, GR activation markedly reduced the size of Schistosoma egg granulomas and substantially repressed the transcription of key Th2-related cytokines, such as IL-4, IL-5, and IL-13. In vitro, GR activation inhibited the transcription of IL-4, IL-5, and IL-13, as well as the secretion of IL-4 in Th2 cells. An integrated analysis of RNA sequencing and single-cell sequencing revealed that GR activation downregulated the expression of two major transcription factors, Gata3 and Pparg, which were elevated in infected mouse livers and Th2 cells but decreased following dexamethasone treatment.ConclusionGR activation may suppress the Th2 immune response triggered by egg antigens by downregulating the expression of the key transcription factors Gata3 and Pparg. While these findings provide insights into a potential complementary therapeutic strategy, further research is necessary to assess the feasibility and safety of targeting GR activation for the treatment of schistosomiasis.